Peran Adopsi Teknologi Informasi dan Inovasi Produk Dalam Memperkuat Keunggulan Bersaing Pada UMKM di Provinsi Sumatera Barat Saat Pandemi - Danny Hidayat (Fakultas Ekonomi Universitas Andalas, 2021)
The Industrial Revolution 4.0 (IR4.0) requires companies and MSMEs to increase their competitiveness, even during the COVID-19 pandemic, apart from adopting information technology, MSMEs also need to innovate products. Small Medium-Sized Enterprises (SMEs) or often known as Micro, Small and Medium Enterprises (MSMEs) in the national economy have an important and strategic role. The rise of Covid-19 has had a huge impact on MSMEs, starting from controlling the curfew by the security forces which resulted in a decrease in sales to the bankruptcy of MSME actors. The urgency of increasing the competitiveness of MSME actors is the background for researchers to raise this title where this competitive advantage can be increased by adopting information technology and innovating products on these MSMEs. This study uses a quantitative research design with the research sample being MSME actors in West Sumatra and in this study the data analysis method uses Smart PLS 3.2.8 software. The results show that the adoption of information technology and product innovation has a positive and significant impact on competitive advantage. Keywords: Competitive Advantage, Information Technology Adoption, Product Innovation